Association of Islet Amyloid Polypeptide and Inflammatory Markers in Type 2 Diabetes Mellitus - Zunjarrao Ganpat Badade; Yogita Mahendra Shinde; Shibban K Kaul; Sandeep Rai; Sameer Kadam (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Islet Amyloid Polypeptide (IAPP) is co-synthesised and co-secreted with insulin by islets of pancreatic β-cells, its increased concentration in individuals with type 2 diabetes mellitus, may involve in inflammatory processes. Aim: To study and find the association of IAPP with inflammatory markers including high-sensitivity C-reactive protein (hsCRP), Tumor Necrosis Factor (TNF)-a and Interleukin(IL)-6 in patients with type 2 diabetes mellitus. Materials and Methods: This was a cross-sectional study, conducted from, December 2015 to December 2019, on 262 subjects (30-60 years, 147 males and 115 females), including 131 healthy controls and 131 known cases of type 2 diabetes mellitus, Fasting blood glucose and glycated haemoglobin(HbA1c) was estimated by commercially available kit, and serum fasting insulin, IAPP, hsCRP, TNF-α, and IL-6 were analysed by ELISA. Insulin Resistance (IR) and insulin sensitivity were calculated. Statistical analysis was done with Statistical Package Social Sciences (SPSS) version 24 the descriptive statistics were expressed as Mean±SD, Student t-test was applied, and p≤0.05 was considered as statistically significant and highly significant at ≤0.01 at 95% CI. The relationship between IAPP and other variables were done by using Spearman Rank correlation (r). Results: Circulatory level of IAPP was positively associated with serum hsCRP (r=0.312, p≤0.05) in type 2 diabetes mellitus. The elevated levels of IAPP (21.3±10.54pmol/l), insulin (11.74±3.91μU/ml), Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) (5.11±2.01) and inflammatory markers including hsCRP (3.44±1.77mg/l), TNF-α (29.5±4.7pg/ml) and IL-6 (20.2±5.2pg/ml) p≤0.05 with poor glycaemic control (HbA1c 8.78±2.30%, p<0.001), and reduced insulin sensitivity {Quantitative Insulin Sensitivity Check Index (QUICKI) 0.31±0.02, p≤0.05} were compared with healthy control; indicates that hyperamylinemia may induce inflammation in individuals with T2DM. Conclusion: Elevated degree of IAPP can be an important predictor and indicator of inflammatory processes and IR in uncontrolled diabetes.